Population Ecology of Caribou in British Columbia - Seip, D.R.; Cichowski, D.B. (Rangifer, 1996)
The abundance and geographic range of woodland caribou (Rangifer tarandus caribou) decreased in many areas of British Columbia during the 1900's. Recent studies have found that predation during the summer is the major cause of mortality and current population declines. Increased moose {Alecs alces) populations may be related to past and current caribou declines by sustaining greater numbers of wolves (Canis lupus). Mortality rates were greater in areas where caribou calved in forested habitats, in close proximity to predators and moose. Caribou populations which had calving sites in alpine areas, islands, and rugged mountains experienced lower mortality and were generally stable or increasing. A predator-induced population decline in one area appeared to stabilize at low caribou densities, suggesting that the wolf predation rate may be density dependent.